ALTERNATIF PENGGUNAAN PASIR LAUT PACIRAN SEBAGAI BAHAN SUSUN ASPAL PANAS AC-WC - Prima Eko Agustyawan; Indra Setia Wiguna (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
The aims of this study are to know the effect of sand sea compound on asphalt (Ac-Wc), (2) To know the trial outcome of sand sea compound at Paciran on hot adpal (Ac-Wc).The research method is experimental research. The experiment object which made for each increasing percentages are three samples, trial by using 1 mold 1100 grams. The result of this research is the variation of sand sea substitution 0%, 50%, 75%, and 100% from soft electric generator weight shown the value of Marshall Properties ideal calculate by using equation regression model with highest decision index. On that equation model got the determination index value (R2) = 1. On the Highest Marshall Properties is 30 percent of sand sea substitution which Marshall parameter consists of Stability 1029.27 kg, VIM 5.07%, VMA 16.35%, VFWA 81.36%, Flow 2.98 mm, Marshall Question 343.85%. From these results, the substitution of 30% sea sand fulfills criteria in Indonesian national standards.Keywords: Sea sand, hot asphalt (AC-WC)